Congestion and Distribution of Rents in Wheat Export Sector: A Canada–U.S. Cross‐Border Comparison. (10th May 2018) - Serfas, Devin; Gray, Richard; Slade, Peter
Abstract: In Canada, average grain freight rates are regulated via the Maximum Revenue Entitlement (MRE), while on the US side of the border grain rates are subject to very little oversight. We use this natural experiment to explore how the MRE regulation has impacted freight rates and the distribution of rents in the wheat supply chain since 2012. On both sides of the border, when large crops have exceeded the short‐term capacity of grain export channels to move the crop, export basis has increased and reduced producer prices. In locations not subject to barge competition, US grain freight rates are higher than Canadian rates and are bid up further during periods of congestion. In Canada, MRE regulation redistributes rents away from railways toward grain companies and producers. These higher grain handling margins have increased the incentives to build additional port terminal capacity in the post‐CWB single desk environment. Au Canada, les tarifs marchandises moyens des céréales sont règlementés par le Revenu admissible maximal (RAM), tandis qu'aux États‐Unis, les tarifs céréaliers font l'objet de très peu de suivi. Au moyen de cette expérience naturelle, nous explorons l'impact du RAM sur les tarifs marchandises et sur la distribution des rentes dans la chaine d'approvisionnement du blé depuis 2012. Des deux côtés de la frontière, lorsque de vastes cultures ont excédé la capacité à court terme des voies d'exportation céréalières pour distribuer leurs récoltes, le seuil d'exportation augmente et réduit les prix des producteurs. Là où ils ne sont pas assujettis à la compétition de barges, les tarifs marchandises céréaliers américains s'avèrent plus élevés que les tarifs canadiens et se voient encore surenchéris lors de période de congestion. Au Canada, la règlementation du RAM redirige les rentes des compagnies ferroviaires aux entreprises et producteurs céréaliers. Ces marges de manutention plus élevées ont augmenté les incitatifs pour accroître la capacité des ports‐terminaux dans un environnement à pupitre unique, post Commission canadienne du blé.